Educación superior y sostenibilidad. El desafío del financiamiento en Argentina - Arias-Valle, María Belén; Marimon, Frederic (Pontificia Universidad Católica del Perú, 2025)
Adequate financing for sustainability in higher education institutions (HEIs) is crucial for advancing the implementation of policies that address social, economic, and environmental challenges of the 21st century. This paper analyzes the regulatory frameworks and financial practices of HEIs in Argentina, evaluating their impact on the institutions' ability to develop and sustain sustainability policies. Through a comprehensive analysis of national legislation, international reports, and academic literature, the study identifies the main barriers and opportunities within the Argentine context. The results reveal that, although the Law 27.621 of 2021 provides a regulatory framework for environmental education, the lack of clear financing mechanisms has led to a fragmented implementation of sustainability policies across Argentine HEIs. In contrast with international models, specific and sustained funding, as well as public-private collaboration, are essential to ensure equity and effectiveness in policy implementation. The article concludes that overcoming current limitations requires reforming the Argentine regulatory framework to incorporate dedicated financing mechanisms that promote strategic partnerships and establish monitoring and evaluation systems. These measures will enable Argentine HEIs to advance more decisively towards an educational model aligned with the Sustainable Development Goals (SDGs).

El financiamiento adecuado para la sostenibilidad en las instituciones de educación superior (IES) es crucial para impulsar la implementación de políticas que aborden los desafíos sociales, económicos y ambientales del siglo XXI. Este artículo analiza los marcos regulatorios y las prácticas financieras de las IES en Argentina, evaluando su impacto en la capacidad de las instituciones para desarrollar y mantener políticas de sostenibilidad. Mediante un análisis exhaustivo de la legislación nacional, informes internacionales y literatura académica, el estudio identifica las principales barreras y oportunidades dentro del contexto argentino. Los resultados revelan que, si bien la Ley 27.621 de 2021 proporciona un marco regulatorio para la educación ambiental, la falta de mecanismos de financiamiento claros ha llevado a una implementación fragmentada de las políticas de sostenibilidad en las IES argentinas. En contraste con los modelos internacionales, la financiación específica y sostenida, así como la colaboración público-privada, son esenciales para garantizar la equidad y la eficacia en la implementación de las políticas. El artículo concluye que superar las limitaciones actuales requiere reformar el marco regulatorio argentino para incorporar mecanismos de financiación dedicados que promuevan asociaciones estratégicas y establezcan sistemas de seguimiento y evaluación. Estas medidas permitirán a las IES argentinas avanzar de manera más decisiva hacia un modelo educativo alineado con los Objetivos de Desarrollo Sostenible (ODS).
Higher Education and Sustainability. The Challenge of Financing in Argentina
Keywords: Education for Sustainable Development; Educational financing; University sustainability; Public Policy; Argentina; Educación para el desarrollo sostenible; Financiamiento educativo; Sostenibilidad universitaria; Política pública; Argentina; https://purl.org/pe-repo/ocde/ford#2.07.01